The Causes of Unpopularity of the Traditional Medicine. - Supasilapa, Somsong; Sinsuphan, Narumon; Ratanasiri, Amornrat (Srinagarind Medical Journal, 2013)
The main objective of this study was to investigate the principal causes of unpopularity of the traditional medicine. Research design was description research using document analysis, depth-interview and participant observation of traditional medicine treatment to obtained the truth as much as possible. Depth-interviews were performed with 30 patients who dislike traditional medical treatment (or who had failed from that), 30 ex-traditional practitioners and persons who are heedful in traditional medicine. The result of this study revealed that there are five factors effecting unpopularity of the traditional medicine as follow:-1) socio-economic status factor of traditional doctor. 2) poor curative efficiency. 3) teaching and education system of traditional doctor. 4) law factor and distribution of government health service system. 5) new technology and improving of western medicine.